Green extraction using natural deep eutectic solvents for determination of As, Cd, and Pb in plant and food matrices by ICP-MS - Brito, Thomas A. [UNESP]; Costa, Floriatan Santos; Oliveira, Rodolpho C. [UNESP]; Amaral, Clarice D.B.; Labuto, Geórgia; Gonzalez, Mario Henrique [UNESP] (Elsevier, 2025)
In this study, extraction methods using natural deep eutectic solvents (NADES) were proposed for the determination of arsenic (As), cadmium (Cd), and lead (Pb) in plant and food matrices. NADES are green and sustainable solvents with advantageous chemical properties for such applications. The NADES were prepared with different components, characterized, and applied in ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE) methods. Experimental variables including temperature, extraction time, and sample-solvent ratio, were investigated using experimental designs to establish the optimal extraction conditions before analysis by ICP-MS. For the MAE method, the optimal conditions were extraction temperature of 100 °C, extraction time of 40 min, and SSR of 40:1 m v−1, resulting in recoveries of up to 84 %. For the UAE method, the optimal conditions were 40 °C, 40 min, and sample-solvent ratio (SSR) of 30:1 m v−1, with recoveries ranging from 96 % to 109 %, all with relative standard deviations less than 11 %. The proposed methods provided low detection limits (mg kg−1), with values of <0.0160 for As, <0.0030 for Cd, and < 0.0090 for Pb for UAE and MAE. The methods were considered green, achieving scores of 0.54 (MAE) and 0.45 (UAE) on the analytical greenness metric for sample preparation. The use of NADES as efficient extractants, combined with multivariate optimization, resulted in optimal experimental conditions, good analytical performance, and enhanced sustainability. The proposed method is a promising approach for applications in food safety and public health studies.
Keywords: Green analytical chemistry; Sample preparation; Sustainable solvents; Toxic inorganic elements